Treponema denticola chymotrypsin‐like proteinase is present in early‐stage mobile tongue squamous cell carcinoma and related to the clinicopathological features. (27th May 2018) - Listyarifah, Dyah; Nieminen, Mikko T.; Mäkinen, Laura K.; Haglund, Caj; Grenier, Daniel; Häyry, Valtteri; Nordström, Dan; Hernandez, Marcela; Yucel‐Lindberg, Tülay; Tervahartiala, Taina; Ainola, Mari; Sorsa, Timo; et al.
Abstract : Background: Certain periodontopathogenic bacteria have been linked to cancers. Treponema denticola ( Td) is associated with severe periodontitis. Chymotrypsin‐like proteinase (CTLP), a major virulence factor of Td, can degrade various host proteins and peptides, and modulate inflammatory responses. However, the role of Td in the tongue carcinogenesis remains unknown. This study aimed to investigate the presence of Td ‐CTLP in early‐stage mobile tongue squamous cell carcinoma (MTSCC) and its relation to clinical and pathological characteristics. Methods: The immunopositivity of Td‐ CTLP was assessed in samples obtained from 60 patients with MTSCC and associated with their clinicopathological data. Additionally, Td ‐CTLP expression was compared with immunoexpression of matrix metalloproteinases (MMP‐8 and MMP‐9), toll‐like receptors (TLR‐2, TLR‐4, TLR‐7 and TLR‐9), c‐Myc, Ki‐67, Bmi‐1 and Snail. Results: Treponema denticola ‐chymotrypsin‐like proteinase was present in 95% of MTSCC tumours of which many (40.4%) showed high immunopositivity. Td‐ CTLP positivity was significantly associated with invasion depth, tumour diameter and the expression of TLR‐7, TLR‐9 and c‐Myc. High Td‐ CTLP immunopositivity in younger patients (≤ 60 years old) predicted early relapse. Conclusion: Our data indicate that Td and its CTLP are present in early‐stage MTSCC carcinoma and may contribute to carcinogenesis, and therefore provide novel perspectives into intervention and therapeutic measures of MTSCC.